Association between the PNPLA3 (rs738409 C>G) variant and hepatocellular carcinoma: Evidence from a meta‐analysis of individual participant data. Issue 6 (25th April 2014) - Trépo, Eric; Nahon, Pierre; Bontempi, Gianluca; Valenti, Luca; Falleti, Edmondo; Nischalke, Hans‐Dieter; Hamza, Samia; Corradini, Stefano Ginanni; Burza, Maria Antonella; Guyot, Erwan; Donati, Benedetta; Spengler, Ulrich; et al.
<x xml:space="preserve">Abstract</x> The incidence of hepatocellular carcinoma (HCC) is increasing in Western countries. Although several clinical factors have been identified, many individuals never develop HCC, suggesting a genetic susceptibility. However, to date, only a few single‐nucleotide polymorphisms have been reproducibly shown to be linked to HCC onset. A variant (rs738409 C>G, encoding for p.I148M) in the PNPLA3 gene is associated with liver damage in chronic liver diseases. Interestingly, several studies have reported that the minor rs738409[G] allele is more represented in HCC cases in chronic hepatitis C (CHC) and alcoholic liver disease (ALD). However, a significant association with HCC related to CHC has not been consistently observed, and the strength of the association between rs738409 and HCC remains unclear. We performed a meta‐analysis of individual participant data including 2, 503 European patients with cirrhosis to assess the association between rs738409 and HCC, particularly in ALD and CHC. We found that rs738409 was strongly associated with overall HCC (odds ratio [OR] per G allele, additive model = 1.77; 95% confidence interval [CI]: 1.42‐2.19; P = 2.78 × 10−7). This association was more pronounced in ALD (OR = 2.20; 95% CI: 1.80‐2.67; P = 4.71 × 10−15) than in CHC patients (OR = 1.55; 95% CI: 1.03‐2.34; P = 3.52 × 10−2). After adjustment for age, sex, and body mass index, the variant remained strongly associated with HCC. Conclusion: Overall, these results suggest that rs738409 exerts a marked influence on hepatocarcinogenesis in patients with cirrhosis of European descent and provide a strong argument for performing further mechanistic studies to better understand the role of PNPLA3 in HCC development. (Hepatology 2014;59:2170–2177)